Aspects of natural history in a sand boa, Eryx muelleri (Erycidae) from arid savannahs in Burkina Faso, Togo, and Nigeria (West Africa). Issue 11 (26th March 2016) - Vignoli, Leonardo; Segniagbeto, Gabriel Hoinsoudé; Eniang, Edem A.; Hema, Emmanuel; Petrozzi, Fabio; Akani, Godfrey C.; Luiselli, Luca
Abstract: The ecology of West African arid savannah snakes is still poorly known, especially in regard to the fossorial species. Here, field data on distribution, morphometrics, habitat use and diet are reported for the sand boa Eryx muelleri (Erycidae) from three different countries, i.e. Burkina Faso, Togo and Nigeria. This snake was observed in 21 distinct localities, and a total of 39 individuals was recorded. The species is likely fairly common and locally abundant. Mean body length of snakes was similar among countries and between sexes, but males had proportionately longer tails than females. Body length was significantly positively correlated with both tail length and head length. Adult sex ratio was close to parity. Most of the specimens were found in well-vegetated spots with low percentage of bare soil. There were apparently both ontogenetic and intersexual dietary variations: (1) a single analysed juvenile fed upon a small-sized lizard, whereas adults fed considerably upon young rodents; and (2) females fed exclusively upon young rodents and males upon both lizards and young rodents. In conservation terms, the species is actively exported from Togo for the pet trade, and additional individuals may also be illegally collected in other countries.